Spectrum of SARS-CoV-2-Related Clinical Syndromes in Children: A Year in the Life. (February 2022) - Khan, Mahjabeen; Dang, LeQuan; Singh, Harjinderpal; Dalrymple, Austin; Miller, Aaron; Tanios, Aline
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has a wide pediatric clinical spectrum. Initial reports suggested that children had milder symptoms compared with adults; then diagnosis of multisystem inflammatory syndrome in children (MIS-C) emerged. We performed a retrospective cohort study of hospitalized patients at a children's hospital over 1 year. Our objectives were to study the demographic and clinical profile of pediatric SARS-CoV-2-associated diagnoses. Based on the clinical syndrome, patients were classified into coronavirus disease 2019 (COVID-19; non-MIS-C) and MIS-C cohorts. Among those who tested positive, 67% were symptomatic. MIS-C was diagnosed in 24 patients. Both diagnoses were more frequent in Caucasians. Both cohorts had different symptom profiles. Inflammatory markers were several-fold higher in MIS-C patients. These patients had critical care needs and longer hospital stays. More COVID-19 patients had respiratory complications, while MIS-C cohort saw cardiovascular involvement. Health care awareness of both syndromes is important for early recognition, diagnosis, and prompt treatment.